IMPLEMENTASI POWER SEARCHING DENGAN SIMBOL MATEMATIKA UNTUK OPTIMALISASI HASIL PENCARIAN REFERENSI PADA SISWA SMKN II TALUK KUANTAN - Diki Arisandi; Sukri sukri; salamun salamun; Roni Salambue (LPPM Universitas Abdurrab, 2017)
Access to information from the internet is become the thing that is needed by almost all society, and also the student of SMK N II Taluk Kuantan. In this community service, the material that has been given is about how the search results obtained to be more effective by using power searching. Power searching delivered to students of SMK N II Taluk Kuantan is by inserting mathematical symbols on the keywords entered into the search engine on the internet. In addition, the material also discussed about more specific search by combining mathematical symbols, host names and file types to search. The method In this community service was giving the material and demo about how the implementation of power searching on search engines. After this activity is implemented, the community service team evaluates the material that has been given before. The result was the students in SMK N II Taluk Kuantan can implement power searching well.\